Pengembangan Buku Ajar Keragaman Budaya Kota Solo untuk Materi IPS Kelas IV - Sholikha, Sofia Nafiatu (FKIP, PGSD, Universitas Slamet Riyadi, 2025)
Cultural diversity characterizes the Indonesian nation and distinguishes it from other nations. Indonesian cultural diversity must be introduced to the younger generation so that it is not foreign. Educational efforts about cultural diversity in elementary schools can be obtained in class IV Natural and Social Sciences subjects. Solo, or Surakarta, is a city in the Central Java Province of Indonesia that has cultural diversity. The need for teaching books in cultural diversity material makes researchers want to make teaching books in this material. The development model used is the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). This research was only carried out up to the development stage; this was due to the limited budget of the researchers. The data collection technique in this study was a validation questionnaire. There are two validators who assess this product, namely media expert validators and material expert validators. This research is intended for elementary school students, especially at Al Hilal Kartasura Islamic Elementary School. The results of the media validation test were 94%, or very feasible, and the material validation test was 84%, or very feasible.